A critical role for virus-specific CD8(+) CTLs in protection from Theiler’s virus-induced demyelination in disease-susceptible SJL mice - Getts, Meghann Teague (2010)
Theiler’s murine encephalomyelitis virus (TMEV)-induced demyelinating disease (TMEV-IDD) is a relevant mouse model of multiple sclerosis. Infection of susceptible SJL/J mice leads to life-long CNS virus persistence and development of a chronic T cell-mediated autoimmune demyelinating disease triggered via epitope spreading to endogenous myelin epitopes. Potent CNS-infiltrating CD8(+) T cell responses to TMEV epitopes have previously been shown to be induced in both disease-susceptible SJL/J and resistant C57BL/6 mice, in which the virus is rapidly cleared. Specific tolerization of SJL CD8(+) T cells specific for the immunodominant TMEV VP3(159–166) epitope has no effect on viral load or development of clinical TMEV-IDD, but adoptive transfer of activated CD8(+) VP3(159–166)-specific T cell blasts shortly after TMEV infection to boost the early anti-viral response leads to clearance of CNS virus and protection from subsequent TMEV-IDD. These studies have important implications for vaccine strategies and treatment of chronic infections in humans.